Kandungan Nitrat, Fosfat Dan Pertumbuhan Biomassa Basah Kiambang (Salvinia molesta) Di Perairan Danau Buyan, Buleleng, Bali - Purnamawati, Ni Wayan Indah; Arthana, I Wayan; Saraswati, Suprabadevi Ayumayasari (Journal of Marine and Aquatic Sciences; Vol 5 No 1 (2019), 2018)
The objective of this research was to determined the relationship between nitrate and phosphate content on the growth of wet biomass Salvinia molesta in Buyan Lake, and also to know the difference of growth of Salvinia molesta in each station with different treatment. The research was conducted from February to March 2017 at Buyan Lake. Biomass measurements and water sampling were carried out at 4 stations with a plot of each treatment. The measurement of wet-biomass were carried out in situ by measuring at each treatment and for measuring the nitrate and phosphate content performed in the laboratory. The result showed that nitrate correlated with biomass growth of Salvinia molesta at the lowest treatment with R 2 value of 0,105 and the  highest at quarter treatment with value R 2 of 0,889. The phosphate relationship with the lowest wet biomass growth was at full treatment with the R 2 value of 0.042 and the highest in the quarter treatment with the R 2 value of 0.936. The highest growth was found in station 1 and the lowest growth at station 4. For each treatment, the highest growth treatment was in a quarter treatment.